2022
DOI: 10.1186/s12916-022-02544-5
|View full text |Cite
|
Sign up to set email alerts
|

Early onset of immune-mediated diseases in minority ethnic groups in the UK

Abstract: Background The prevalence of some immune-mediated diseases (IMDs) shows distinct differences between populations of different ethnicities. The aim of this study was to determine if the age at diagnosis of common IMDs also differed between different ethnic groups in the UK, suggestive of distinct influences of ethnicity on disease pathogenesis. Methods This was a population-based retrospective primary care study. Linear regression provided unadjuste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…SAD predilects females and usually arises during the adolescence or young adulthood [ 9 ]. The high prevalence of certain ethnicities confirms previous epidemiological studies that have shown that the odds for SAD is higher, and the mean age of disease onset is lower, in Black Africans and Asians compared to Whites [ 10 , 11 ]. The earlier onset of SAD implies a longer exposure to the inflammatory state that eventually favors an early AF onset with potential anticipation of cardiovascular events.…”
Section: Discussionsupporting
confidence: 84%
“…SAD predilects females and usually arises during the adolescence or young adulthood [ 9 ]. The high prevalence of certain ethnicities confirms previous epidemiological studies that have shown that the odds for SAD is higher, and the mean age of disease onset is lower, in Black Africans and Asians compared to Whites [ 10 , 11 ]. The earlier onset of SAD implies a longer exposure to the inflammatory state that eventually favors an early AF onset with potential anticipation of cardiovascular events.…”
Section: Discussionsupporting
confidence: 84%
“…However our multiple linear regression model revealed that neither multimorbidity nor BMI contributed signi cantly to the IMM-AGE score, instead South Asian ethnicity contributed to 17% of the increase in the IMM-AGE score. Interestingly we have shown recently that South Asians adults develop a broad range of immune-mediated diseases much earlier than white adults, possibly suggesting that their immune systems age more rapidly [44]. Our data thus suggest that the SARS-CoV2 infection itself results in an increase in immune ageing.…”
Section: Discussionmentioning
confidence: 51%
“…[22] In contrast, our study showed a signi cant relationship between IBD and COVID-19 vaccines, suggesting that this inconsistency in results is due to the distinct in uences of ethnicity on autoimmune responses. [23] AID differs between ethnic groups, and the incidence of IBD in Asian populations is much lower than that in Western populations.…”
Section: Discussionmentioning
confidence: 96%